Promoting Academic Success Among African American and Hispanic College Students - Stephanie Jones; Kimberley Gordon-Biddle; Julianna Raskauskas (Adult Education Research Conference, 2011)
This study investigates the significant types of social support being offered to Black and Hispanic students attending a diverse institution of higher education with low Black and Hispanic student enrollment. The sample consists of 43 Black and 30 Hispanic students. Results indicate that both Black and Hispanic students believe close-friendship, faculty, and classmate support to impact their academic achievement. Results from this study support previous research and can benefit trainers, administrators, and instructors.